A new species of solitary Entoprocta (Loxosomatidae) from mangroves of Vietnam with close affinity to Loxomitra - Borisanova, Anastasia O. (Zootaxa, 2026)
The new species of solitary entoproct, Loxosomella incurva sp. nov., is described from the Cần Giờ Mangrove Forest, located in the south coastal region of Vietnam. This is the first description of a member of the Loxosomatidae from Vietnamese waters and from the mangrove ecosystems. The specimens of Loxosomatidae were found on the polychaete of the family Acoetidae. Loxosomella incurva sp. nov. is a medium-sized species with a characteristically curved body—the calyx is inclined toward the short stalk. The calyx bears seven or eight tentacles. Four (or five) sensory papillae are located along the edge of the calyx. Specimens attach to the host’s body with an elongated narrow platform at the end of the stalk. Buds lack a pedal disc or a creeping foot and instead possess a unique annular bulge. Molecular phylogenetic analyses of partial sequences of two genetic markers, 28S rRNA and 18S rRNA, revealed a close relationship between L. incurva sp. nov. and two species of the subgenus Loxomitra, L. (L.) tetraorganon and L. (L.) mizugamaensis. Loxosomella incurva sp. nov. does not possess the diagnostic morphological features of Loxomitra: its buds lack the wings at the end of the stalk and attach to the maternal specimen by the base of the stalk, rather than by the back of the stalk or calyx as in Loxomitra. A common feature of all three species within this clade is the absence of a foot at the end of the stalk in the bud. The existing system of Loxosomatidae requires revision, since according to molecular genetic data, neither the genus Loxosoma nor the genus Loxosomella are monophyletic. The creeping foot was likely present in the common ancestor of all Loxosomatidae and has been retained in some lineages while modified in others; therefore, its presence cannot serve as a diagnostic generic character.